Annual Report. Transmittal and Summary for the Year 1962-1963 to the Shareholders of the Cincinnati Museum Association - Anonymus, A.
unpaginiert; spez. Libation Bowl Darius, 1963. 31 (1 pl.); Nail Tile Untaš-GAL, 1961. 154 (1 fig.); Foundation Plaque, Artaxerxes II., 1963.32; dto 1963.33 (je 1 fig.); Beaker, Persian, 1962.71 (1 fig.); Relief from Persepolis, 1961.288 (1 fig.).